Association of maternal metals exposure, metabolites and birth outcomes in newborns: A prospective cohort study - Shuangshuang Zhao; Xu Yang; Qing Xu; Hang Li; Yan Su; Qiaoqiao Xu; Qing X Li; Yankai Xia; Rong Shen (Environment International, 2023)
Background: Maternal exposure to metals may pose a risk to the health of newborns, however, the underlying mechanisms remain ambiguous. Herein, we aimed to investigate the influence of metals exposure on birth outcomes and reveal the importance of metabolites in the exposure-outcomes association by using metabolomics methods. Methods: In our study, 292 mother-pairs were included who were recruited from the affiliated hospitals of Nanjing Medical University between 2006 and 2011. We measured fifteen metals (mercury, lead, vanadium, arsenic, zinc, cadmium, rubidium, copper, cobalt, iron, molybdenum, strontium, thallium, magnesium and calcium) and metabolites in maternal second trimester serums by using inductively coupled plasma mass spectrometry and ultra-high performance liquid chromatography high resolution accurate mass spectrometry, respectively. A multi-step statistical analysis strategy including exposome-wide association study (ExWAS) model, variable selection models and multiple-exposure models were performed to systematically appraise the associations of individual and mixed metals exposure with birth outcomes. Furthermore, differential metabolites that associated with metals exposure and birth outcomes were identified using linear regression models. Results: Metal’s levels in maternal serums ranged from 0.05 μg/L to 1864.76 μg/L. In the ExWAS model, maternal exposure to arsenic was negatively associated with birth weight (β = 188.83; 95% CI: −368.27, −9.39), while maternal mercury exposure showed a positive association (β = 533.65; 95%CI: 179.40, 887.90) with birth weight. Moreover, each unit increase in mercury (1 ng/mL-log transformed) was associated with a 1.82 week-increase (95%CI: 0.85, 2.79) in gestational age. These findings were subsequently validated by variable selection models and multiple exposure models. Metabolomic analysis further revealed the significant role of 3-methyladenine in the relationship between arsenic exposure and birth weight. Conclusion: This study provides new epidemiological evidence indicating the associations of metals exposure and neonatal birth outcomes, and emphasizes the potential role of metabolite biomarkers and their importance in monitoring adverse birth outcomes.